2008
DOI: 10.1121/1.2934906
|View full text |Cite
|
Sign up to set email alerts
|

Resonance frequencies of the multilayered piezotransducers

Abstract: metallic blocks and a central bolt that pre-stresses the assembly. The characterization of these transducers has been done by using numerical methods but, in many cases, simplified one-dimensional models are enough to a good physical interpretation of the problem. In this work it was used Mason´s equivalent electric circuit for onedimensional modeling of composed transducers. It was employed Thévenin´s equivalent circuit to simplify the problem and evaluate the effects of the central bolt on the resonances. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It consists of piezoceramic rings sandwiched between matching end and front mass. This construction is mechanically prestressed by a centre bolt, which provides enough preload to the piezo rings to avoid any fractures on the expansion of piezoceramic [5]. One-dimensional and combined vibrations like longitudinal-flexural, longitudinal-torsional, and flexuraltorsional can be generated by a single device and employed on the tool for applications like ultrasonic vibration-assisted drilling, milling, and polishing [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of piezoceramic rings sandwiched between matching end and front mass. This construction is mechanically prestressed by a centre bolt, which provides enough preload to the piezo rings to avoid any fractures on the expansion of piezoceramic [5]. One-dimensional and combined vibrations like longitudinal-flexural, longitudinal-torsional, and flexuraltorsional can be generated by a single device and employed on the tool for applications like ultrasonic vibration-assisted drilling, milling, and polishing [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of piezoceramic rings sandwiched between matching end and front mass. This construction is mechanically prestressed by a centre bolt, which provides enough preload to the piezo rings to avoid any fractures on the expansion of piezoceramic [3]. One-dimensional and combined vibrations like Longitudinal-flexural, Longitudinal-torsional, and flexural-torsional can be generated by a single device and employed on the tool for applications like ultrasonic vibrationassisted drilling, milling, and polishing [4], [5].…”
Section: Introduction -mentioning
confidence: 99%
“…Experimental results indicated that the measured resonance frequency of the transducer was in good agreement with the theoretical value. Arnold (2008) In this paper, the transducer and the horn were designed as a whole, in other words, an ultrasonic transducer with a quarter-wave taper transition horn was designed based on the equivalent circuit method. Meanwhile, the equivalent circuit of the transducer was adopted to obtain its mechanical responses and electrical characteristics.…”
Section: Introductionmentioning
confidence: 99%